A low-density conductive silver paste and preparation method thereof

By developing a low-density conductive silver paste, using silver powder and graphene as conductive particles, and using special curing agents, the problem of high cost of low-temperature curing paste in heterojunction solar cells is solved, and rapid curing is achieved at low temperatures and the effect of high conductivity have promoted the large-scale promotion of solar cells.

CN118841206BActive Publication Date: 2025-02-07JIANGSU RIYU PHOTOVOLTAIC NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411310629.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-07
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

In heterojunction solar cells, the amorphous silicon passivation layer cannot withstand high temperatures, so conventional solar slurry cannot be used. The amount of silver powder added to the low-temperature curing slurry needs to reach 90%, which makes the cost too high, limiting heterojunction solar energy. Large-scale promotion of batteries.

Method used

Develop a low-density conductive silver paste, by using silver powder and graphene as conductive particles, and using a special curing agent, the intermediate is formed by the reaction of benzimidazole and epoxychlorohydrin, and then with pentaerythritol tetrathioglycolate and N,N-dimethylformamide reaction prepares curing agents to ensure rapid curing at low temperatures and improves electrical conductivity.

Benefits of technology

The effect of rapid curing at low temperatures is achieved, the volume resistivity of conductive silver paste is reduced, the conductive and printing performance is improved, the cost is reduced, and the large-scale promotion of heterojunction solar cells is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a low-density conductive silver paste and a preparation method thereof, and relates to the technical field of solar cells. The low-density conductive silver paste comprises the following raw materials in parts by weight: 80-90 parts of silver powder, 3-5 parts of graphene, 2.5-3.8 parts of organic resin, 0.5-1 parts of curing agent, 5-10 parts of solvent, 1.5-3 parts of thixotropic agent, and 1.5-2.5 parts of dispersant; the curing agent not only has a mercapto group for epoxy resin curing in structure, but also the remaining mercapto group after curing can also generate mercapto-silver interaction with nano silver to prevent silver migration; in addition, the secondary amine and tertiary amine on the benzimidazole on the intermediate improve the curing reaction speed of the epoxy resin, thereby shortening the curing time and ensuring that the system can be quickly cured at low temperature; the large conjugated plane of the benzimidazole is tightly combined with the π-π effect between the graphene, thereby improving the dispersibility of the graphene, preventing aggregation, and improving the printing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to a low-density conductive silver paste and a preparation method thereof. Background Art

[0002] Solar cells are photoelectric devices that convert sunlight directly into electrical energy through the photovoltaic effect. Traditional solar cells are crystalline silicon solar cells. In recent years, a heterojunction (Heterojunction with Intrinsic Thin-layer, referred to as HIT) solar cells, HJT cells have a symmetrical double-sided structure, with N-type single crystal silicon in the middle and washed after texturing, and then intrinsic amorphous silicon film and P-type amorphous silicon film are deposited in sequence on the front side by plasma enhanced chemical vapor deposition to form a PN junction, and then intrinsic amorphous silicon film and N-type amorphous silicon film are deposited in sequence on the back side of the single crystal silicon to form a back surface field; due to the poor conductivity of amorphous silicon, transparent conductive oxide film (TCO) is deposited on both sides of the cell by physical vapor deposition or reactive plasma deposition to conduct electricity, and finally the conductive silver paste is printed on the TCO film layer by screen printing technology to form an "H-type" main grid and fine grid lines to solidify to form double-sided contact electrodes. The production process of heterojunction solar cells is relatively simple, the process temperature is low, and it can adapt to thinning, so it can greatly reduce the manufacturing cost of the cell. In addition, heterojunction solar cells also have the characteristics of double-sided power generation, so they have become the main development direction of solar cells.

[0003] Since heterojunction solar cells contain an amorphous silicon passivation layer, they cannot withstand high temperatures, so the solar slurry used for conventional solar cells cannot be used. Instead, a low-temperature curing slurry that cures at low temperatures must be used. Currently, the low-temperature curing slurry used is mainly an epoxy-based silver-containing low-temperature slurry. In order to reduce the volume resistivity of the slurry, the amount of silver powder added usually needs to reach 90%, which makes the cost of the low-temperature slurry too high, which is not conducive to the large-scale promotion of heterojunction solar cells. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a low-density conductive silver paste and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A low-density conductive silver paste comprises the following raw materials in parts by weight: 80-90 parts of silver powder, 3-5 parts of graphene, 2.5-3.8 parts of organic resin, 0.5-1 part of curing agent, 5-10 parts of solvent, 1.5-3 parts of thixotropic agent, and 1.5-2.5 parts of dispersant;

[0007] The curing agent is prepared by the following steps:

[0008] Step S1, adding benzimidazole and epichlorohydrin to a 30-40% ethanol aqueous solution, stirring at a uniform speed and heating to 60-80° C., keeping the temperature for reaction for 2-4 hours, adding dropwise a 10% sodium hydroxide aqueous solution after the reaction, heating to 70-90° C., keeping the temperature for reaction for 4-6 hours, separating the liquids to remove the brine after the reaction, washing with deionized water and then removing the solvent by rotary evaporation to obtain an intermediate, controlling the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide to be 1-2mmol:5-10mmol:3-5mmol, and the volume ratio of epichlorohydrin to the ethanol aqueous solution to be 1:10;

[0009] In step S1, benzimidazole first undergoes a ring-opening reaction with the epoxy group on epichlorohydrin, and then re-cyclizes under alkaline conditions to prepare an intermediate;

[0010] Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N, N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring magnetically and reacting for 4-6 hours, and preparing a curing agent after the reaction is completed, controlling the amount ratio of the intermediate, pentaerythritol tetrathioglycolate and N, N-dimethylformamide to be 1-1.5mmol:1-1.5mmol:10mL, and the amount of N, N-dimethylformamide to be 10-15% of the weight of the intermediate 1.

[0011] In step S2, 2,4,6-tris(dimethylaminomethyl) is used as a promoter, and the epoxy group on the intermediate reacts with the thiol group on pentaerythritol tetrathioglycolate to prepare a curing agent. The curing agent not only has a thiol group for epoxy resin curing in structure, but also the remaining thiol group after curing can also produce a thiol-silver interaction with nanosilver to prevent the migration of nanosilver. In addition, the secondary amine and tertiary amine on the benzimidazole on the intermediate increase the curing reaction speed of the epoxy resin, thereby shortening the curing time and ensuring that the system can be quickly cured at low temperatures. The large conjugated plane of the benzimidazole is tightly combined with the π-π interaction between the graphenes, which solves the problem of strong π-π interaction between the graphenes and easy agglomeration, thereby improving the dispersibility of the graphenes, preventing aggregation, and improving the uniformity of printing.

[0012] Furthermore, the organic resin is bisphenol A epoxy resin E44.

[0013] Furthermore, the solvent is one or more of butyl glycidyl ether, ethyl acetate and benzyl alcohol mixed in any proportion.

[0014] Furthermore, the thixotropic agent is hydrogenated castor oil, and the dispersant is an aliphatic amide dispersant.

[0015] A method for preparing a low-density conductive silver paste comprises the following steps:

[0016] The first step is to add organic resin, thixotropic agent and dispersant into solvent, stir evenly to obtain a mixed solution;

[0017] In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put into a three-roller mill and rolled for 5-6 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

[0018] Beneficial effects of the present invention:

[0019] The present invention prepares a low-density conductive silver paste, wherein silver powder and graphene are used as conductive particles. On the one hand, graphene can increase the contact between the silver powders, and the strong interaction caused by the close contact with the silver powders can improve the transfer efficiency of electrons at the silver powder interface, and the introduced graphene can fill the gaps between the silver powders, further improving the conductive performance. The present invention also prepares a curing agent, wherein benzimidazole first undergoes a ring-opening reaction with the epoxy group on epichlorohydrin, and then re-rings under alkaline conditions to prepare an intermediate, and then the epoxy group on the intermediate reacts with the thiol group on pentaerythritol tetrathioglycolate to prepare a curing agent. A curing agent is prepared. The curing agent not only has a mercapto group for epoxy resin curing in structure, but also the remaining mercapto group after curing can generate mercapto-silver interaction with nano silver to prevent silver migration. In addition, the secondary amine and tertiary amine on the benzimidazole on the intermediate increase the curing reaction speed of the epoxy resin, thereby shortening the curing time and ensuring that the system can be quickly cured at low temperature. The large conjugated plane of the benzimidazole is tightly combined with the π-π interaction between graphene, which solves the problem of strong π-π interaction between graphene and easy agglomeration, thereby improving the dispersibility of graphene, preventing aggregation, and improving printing performance. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1: A low-density conductive silver paste comprises the following raw materials in parts by weight: 80 parts of silver powder, 3 parts of graphene, 2.5 parts of bisphenol A epoxy resin E44, 0.5 parts of curing agent, 5 parts of butyl glycidyl ether, 1.5 parts of hydrogenated castor oil, and 1.5 parts of dispersant.

[0022] The low-density conductive silver paste is prepared by the following steps:

[0023] The first step is to add bisphenol A epoxy resin E44, hydrogenated castor oil and a dispersant into butyl glycidyl ether, and stir evenly to obtain a mixed solution;

[0024] In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put it on a three-roll mill and rolled it for 5 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

[0025] The curing agent is prepared by the following steps:

[0026] Step S1, adding benzimidazole and epichlorohydrin to a 30% ethanol aqueous solution, stirring at a uniform speed and heating to 60° C., keeping the temperature for reaction for 2 hours, adding dropwise a 10% sodium hydroxide aqueous solution after the reaction, heating to 70° C., keeping the temperature for reaction for 4 hours, separating the liquids to remove the brine after the reaction, washing with deionized water and then removing the solvent by rotary evaporation to obtain an intermediate, controlling the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide to be 1 mmol: 5 mmol: 3 mmol, and the volume ratio of epichlorohydrin and ethanol aqueous solution to be 1: 10;

[0027] Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N, N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring magnetically and reacting for 6 hours, and preparing a curing agent after the reaction is completed, controlling the amount ratio of the intermediate, pentaerythritol tetrathioglycolate and N, N-dimethylformamide to be 1 mmol: 1 mmol: 10 mL, and the amount of N, N-dimethylformamide is 10% of the weight of the intermediate 1.

[0028] The dispersant is an aliphatic amide dispersant Dumeen TDO.

[0029] Example 2: A low-density conductive silver paste comprises the following raw materials in parts by weight: 85 parts of silver powder, 4 parts of graphene, 2.8 parts of bisphenol A epoxy resin E44, 0.6 parts of curing agent, 6 parts of ethyl acetate, 2 parts of hydrogenated castor oil, and 1.8 parts of dispersant.

[0030] The low-density conductive silver paste is prepared by the following steps:

[0031] The first step is to add bisphenol A epoxy resin E44, hydrogenated castor oil and a dispersant into ethyl acetate and stir evenly to obtain a mixed solution;

[0032] In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put it on a three-roll mill and rolled it for 5 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

[0033] The curing agent is prepared by the following steps:

[0034] Step S1, adding benzimidazole and epichlorohydrin to a 30% ethanol aqueous solution, stirring at a uniform speed and heating to 65° C., keeping the temperature for reaction for 2 hours, adding dropwise a 10% sodium hydroxide aqueous solution after the reaction, heating to 75° C., keeping the temperature for reaction for 5 hours, separating the liquids to remove the brine after the reaction, washing with deionized water and then removing the solvent by rotary evaporation to obtain an intermediate, controlling the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide to be 1.5 mmol: 6 mmol: 3 mmol, and the volume ratio of epichlorohydrin and ethanol aqueous solution to be 1: 10;

[0035] Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N, N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring magnetically and reacting for 4-6 hours, and preparing a curing agent after the reaction is completed, controlling the amount ratio of the intermediate, pentaerythritol tetrathioglycolate and N, N-dimethylformamide to be 1.2 mmol: 1.2 mmol: 10 mL, and the amount of N, N-dimethylformamide to be 12% of the weight of the intermediate 1.

[0036] The dispersant is an aliphatic amide dispersant.

[0037] Example 3

[0038] A low-density conductive silver paste comprises the following raw materials in parts by weight: 88 parts of silver powder, 4 parts of graphene, 3.5 parts of bisphenol A epoxy resin E44, 0.8 parts of curing agent, 8 parts of benzyl alcohol, 2.5 parts of hydrogenated castor oil, and 2 parts of dispersant.

[0039] The low-density conductive silver paste is prepared by the following steps:

[0040] The first step is to add bisphenol A epoxy resin E44, hydrogenated castor oil and a dispersant into benzyl alcohol, and stir evenly to obtain a mixed solution;

[0041] In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put into a three-roller mill and rolled for 5-6 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

[0042] The curing agent is prepared by the following steps:

[0043] Step S1, adding benzimidazole and epichlorohydrin to a 40% ethanol aqueous solution, stirring at a uniform speed and heating to 70°C, keeping the temperature for reaction for 4 hours, adding dropwise a 10% sodium hydroxide aqueous solution after the reaction, heating to 90°C, keeping the temperature for reaction for 6 hours, separating the liquids to remove the brine after the reaction, washing with deionized water and then removing the solvent by rotary evaporation to obtain an intermediate, controlling the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide to be 1.8mmol:8mmol:5mmol, and the volume ratio of epichlorohydrin and ethanol aqueous solution to be 1:10;

[0044] Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N, N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring magnetically and reacting for 4-6 hours. After the reaction is completed, the curing agent prepared is controlled to have an amount ratio of 1.4 mmol: 1.4 mmol: 10 mL, and the amount of N, N-dimethylformamide is 14% of the weight of the intermediate 1.

[0045] The thixotropic agent is hydrogenated castor oil, and the dispersant is an aliphatic amide dispersant.

[0046] Example 4

[0047] A low-density conductive silver paste comprises the following raw materials in parts by weight: 90 parts of silver powder, 5 parts of graphene, 3.8 parts of bisphenol A epoxy resin E44, 1 part of curing agent, 10 parts of butyl glycidyl ether, 3 parts of hydrogenated castor oil, and 2.5 parts of dispersant.

[0048] The low-density conductive silver paste is prepared by the following steps:

[0049] The first step is to add bisphenol A epoxy resin E44, hydrogenated castor oil and a dispersant into butyl glycidyl ether, and stir evenly to obtain a mixed solution;

[0050] In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put it on a three-roll mill and rolled 6 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

[0051] The curing agent is prepared by the following steps:

[0052] Step S1, adding benzimidazole and epichlorohydrin to a 40% ethanol aqueous solution, stirring at a uniform speed and heating to 80° C., keeping the temperature for 4 hours, adding dropwise a 10% sodium hydroxide aqueous solution after the reaction, heating to 90° C., keeping the temperature for 6 hours, separating the liquids to remove the brine after the reaction, washing with deionized water and then removing the solvent by rotary evaporation to obtain an intermediate, controlling the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide to be 2mmol:10mmol:5mmol, and the volume ratio of epichlorohydrin and ethanol aqueous solution to be 1:10;

[0053] Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N, N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring magnetically and reacting for 4-6 hours. After the reaction is completed, the curing agent prepared is controlled to have an amount ratio of the intermediate, pentaerythritol tetrathioglycolate and N, N-dimethylformamide of 1.5 mmol: 1.5 mmol: 10 mL, and the amount of N, N-dimethylformamide is 15% of the weight of the intermediate 1.

[0054] The dispersant is an aliphatic amide dispersant.

[0055] Comparative Example 1: Compared with Example 1, this comparative example uses polyetheramine D230 as a curing agent, and the rest is the same as Example 1.

[0056] Comparative Example 2: Compared with Example 1, this comparative example uses pentaerythritol tetrathioglycolate and 2,4,6-tris(dimethylaminomethyl) as curing agents, and the preparation method is as follows:

[0057] A low-density conductive silver paste comprises the following raw materials in parts by weight: 80 parts of silver powder, 3 parts of graphene, 2.5 parts of bisphenol A epoxy resin E44, 0.4 parts of pentaerythritol tetrathioglycolate, 0.1 parts of 2,4,6-tris(dimethylaminomethyl), 5 parts of butyl glycidyl ether, 1.5 parts of hydrogenated castor oil, and 1.5 parts of a dispersant.

[0058] The low-density conductive silver paste is prepared by the following steps:

[0059] The first step is to add bisphenol A epoxy resin E44, hydrogenated castor oil and a dispersant into butyl glycidyl ether, and stir evenly to obtain a mixed solution;

[0060] In the second step, silver powder, graphene, pentaerythritol tetrathioglycolate and 2,4,6-tris(dimethylaminomethyl) are added to the mixed solution and stirred for 2 hours, then put it on a three-roll mill and rolled for 5 times. When the scraper fineness is less than 10 μm, it is filtered to obtain a low-density conductive silver paste.

[0061] The conductive pastes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were screen-printed onto the TCO surface of the HJT battery, and cured at 110° C. The curing time was recorded. After curing, the contact resistivity was tested by the TLM method, and the line width was measured using a 3D microscope. The results are shown in Table 1:

[0062] Table 1

[0063]

[0064] It can be seen from Table 1 above that the conductive silver pastes prepared in Examples 1 to 4 of the present invention can be cured quickly, have excellent conductive properties, better printing properties, and less light shielding.

[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A low-density conductive silver paste, characterized in that: The method comprises the following raw materials in parts by weight: 80-90 parts of silver powder, 3-5 parts of graphene, 2.5-3.8 parts of organic resin, 0.5-1 part of curing agent, 5-10 parts of solvent, 1.5-3 parts of thixotropic agent, and 1.5-2.5 parts of dispersant; The curing agent is prepared by the following steps: Step S1, adding benzimidazole and epichlorohydrin to a 30-40% ethanol aqueous solution, stirring at a uniform speed and heating to 60-80° C., and keeping the temperature for reaction for 2-4 hours. After the reaction, adding dropwise a 10% sodium hydroxide aqueous solution, heating to 70-90° C., and keeping the temperature for reaction for 4-6 hours to obtain an intermediate; Step S2, adding the prepared intermediate and pentaerythritol tetrathioglycolate to N,N-dimethylformamide, stirring at a uniform speed and adding 2,4,6-tris(dimethylaminomethyl), stirring with a magnetic stir and reacting for 4-6 hours, and preparing a curing agent after the reaction is completed.

2. A low-density conductive silver paste according to claim 1, characterized in that: The organic resin is bisphenol A epoxy resin.

3. The low-density conductive silver paste according to claim 1, characterized in that: The solvent is one or more of butyl glycidyl ether, ethyl acetate and benzyl alcohol mixed in any proportion.

4. The low-density conductive silver paste according to claim 1, characterized in that: The thixotropic agent is hydrogenated castor oil, and the dispersant is an aliphatic amide dispersant.

5. The low-density conductive silver paste according to claim 1, characterized in that: In step S1, the molar ratio of benzimidazole, epichlorohydrin and sodium hydroxide is controlled to be 1-2mmol:5-10mmol:3-5mmol, and the volume ratio of epichlorohydrin and ethanol aqueous solution is 1:

10.

6. The low-density conductive silver paste according to claim 1, characterized in that: In step S2, the amount ratio of the intermediate, pentaerythritol tetrathioglycolate and N,N-dimethylformamide is controlled to be 1-1.5 mmol:1-1.5 mmol:10 mL, and the amount of N,N-dimethylformamide is 10-15% of the weight of the intermediate.

7. A method for preparing the low-density conductive silver paste according to any one of claims 1 to 6, characterized in that: The steps include: The first step is to add organic resin, thixotropic agent and dispersant into solvent, stir evenly to obtain a mixed solution; In the second step, silver powder, graphene and curing agent are added to the mixed solution and stirred for 2 hours, then put it on a three-roller mill and roll it 5-6 times. When the scraper fineness is less than 10μm, filter it to obtain a low-density conductive silver paste.

Citation Information

Patent Citations

  • Low-temperature conductive silver paste for HIT solar cell and preparation method thereof

    CN110136863A

  • HJT low-temperature conductive silver paste containing silver nano short rods and preparation method of HJT low-temperature conductive silver paste

    CN116564579A